2009
DOI: 10.1111/j.1528-1167.2008.01763.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in GABAA receptor properties in amygdala kindled animals: In vivo studies using [11C]flumazenil and positron emission tomography

Abstract: SUMMARYPurpose: The purpose of the present investigation was to quantify alterations in GABA A receptor density in vivo in rats subjected to amygdala kindling. Methods: The GABA A receptor density was quantified by conducting a [ 11 C]flumazenil (FMZ) positron emission tomography (PET) study according to the full saturation method, in which each animal received a single injection of FMZ to fully saturate the GABA A receptors. Subsequently, the concentration-time curves of FMZ in blood [using highpressure liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 46 publications
3
23
0
Order By: Relevance
“…Results suggested that receptor density, B max , was lower in kainate-treated animals than in controls. This result is in line with previous preclinical and clinical studies using 11 C-flumazenil (17,22) and suggests a reduction in GABA A receptor binding capacity in the epileptic brain, compared with the naïve brain. A previous study in kindled rats, another rat model for temporal lobe epilepsy (23,24), showed that B max was reduced by 36%, compared with controls (17).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Results suggested that receptor density, B max , was lower in kainate-treated animals than in controls. This result is in line with previous preclinical and clinical studies using 11 C-flumazenil (17,22) and suggests a reduction in GABA A receptor binding capacity in the epileptic brain, compared with the naïve brain. A previous study in kindled rats, another rat model for temporal lobe epilepsy (23,24), showed that B max was reduced by 36%, compared with controls (17).…”
Section: Discussionsupporting
confidence: 82%
“…(27), and 54.5 ngÁmL 21 in rat brain homogenates (28). The K D estimate, 5.9 6 0.9 ngÁmL 21 , obtained in the present study is also in line with previously published studies (17,18,(25)(26)(27)(28). On the basis of time-activity data obtained in a previous study when 11 C-flumazenil was administered without the addition of unlabeled flumazenil (18), the doses used in the present study resulted in approximate occupancy levels of 30%-40% for 4-mg, 60%-70% for 20-mg, 70%-80% for 100-mg, and around 90% for 400-mg dose groups.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Metabolic neuroimaging with positron emission tomography (PET) is the most widely used diagnostic, (for review (Mirrione and Tsirka, 2011). A handful of recent studies in animal models have also begun to utilize specific radioligands studying GABA, serotonin, dopamine, and the cannabinoid systems (Werhahn et al, 2006, Goffin et al, 2008a, Liefaard et al, 2009, Liew et al, 2009, Assem-Hilger et al, 2010. There are also a few pilot studies in the literature examining the acetylcholine (Mohamed et al, 2005) and opioid systems (Theodore et al, 1992) in epilepsy patients.…”
Section: Neuroimaging As a Potential Tool For Exploring In Vivo Functmentioning
confidence: 99%